‘Our Gracious Benefactors’: The Charitable Activities of the Vilnius Cathedral Chapter in the Sixteenth to Eighteenth Centuries - Jakulis, Martynas (History / Istorija, 2019)
Using the acts of the cathedral chapter and annual income-expenditure registers, this article focuses on the charitable activities of the Vilnius Cathedral Chapter in the sixteenth to eighteenth centuries. The first section of the article is concerned with the chapter’s support for charitable institutions (hospitals, a dowry fund, a home for aged and infirm priests) under its patronage. The second section focuses on the patterns of occasional almsgiving.